2010
DOI: 10.1002/adma.201003805
|View full text |Cite
|
Sign up to set email alerts
|

V2O5 Loaded on SnO2 Nanowires for High‐Rate Li Ion Batteries

Abstract: The growing demand for high-power applications such as electric vehicles, hybrid electric vehicles, and other power-supply devices has triggered signifi cant research efforts on high-energy and power-density energy-storage devices. [1][2][3][4][5] Among the energystorage devices, electrochemical supercapacitors can deliver high power, but they suffer from low energy density. [ 5 ] Lithium batteries (LiBs) with their high energy density have attracted considerable attention. [6][7][8][9] However, for use as a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 28 publications
3
120
1
Order By: Relevance
“…However, even though many different synthetic methods have been for such architectures, most of these generally lead to the formation of 1D hierarchical heterostructures through solution methods. [8][9][10][11] Therefore, the development of facile and simple methods suitable for the fabrication of novel 1D nanomaterials still remains as a great challenge. Recently, as a kind of promising technique, electrospinning has been widely used as a convenient and cost-effective method to generate a variety of 1D nanomaterials with unique morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, even though many different synthetic methods have been for such architectures, most of these generally lead to the formation of 1D hierarchical heterostructures through solution methods. [8][9][10][11] Therefore, the development of facile and simple methods suitable for the fabrication of novel 1D nanomaterials still remains as a great challenge. Recently, as a kind of promising technique, electrospinning has been widely used as a convenient and cost-effective method to generate a variety of 1D nanomaterials with unique morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…As references, Rct of the V2O5 nanoparticle electrode ( Figure S12a) increased obviously from 1.4 to 4.5 kΩ, and similarly, Rct of the V2O5 nanosheet array electrode increased from 71 to 168 Ω during the cycling process from 100th to 5000th cycle ( Figure S12b), which should be associated with the deterioration of electron transport due to the formation of disconnected clusters by aggregation of nanoparticles and gradual array collapse during cycling. [32,46,49] Moreover, Rs of the V2O5 nanosheet array electrode increased from 6.4 to 22.5 Ω from 100th to 5000th cycle, which could be caused by the dissolution of active materials into electrolyte during cycling processes. In comparison with the V2O5 nanoparticle and the V2O5 nanosheet array electrodes, the V2O5/3DC-CFs composite shows the smallest change in Rct during long cycling.…”
Section: Figurementioning
confidence: 99%
“…[17,29] Recently, it was shown that direct growth of V2O5 array structures on a current collector can substantially reduce the interparticle resistance and contact resistance, and leads to improved capacity and cyclic stability. [30][31][32] However, the low areal loading of the V2O5 array structures (~0.7 mg cm -2 ), hindered their practical application. [33] Moreover, collapse of the V2O5 array structures upon repeated charge/discharge cycling is another important problem to be addressed for high-performance LIBs.…”
mentioning
confidence: 99%
“…The good performance is explained by electric double layer capacitance of large surface area and high rate lithium insertion to V 2 O 5 gel. Recently, Yan et al (2011) have adopted a simple gas-phase-based method to synthesize V 2 O 5 loaded SnO 2 nanowires on the stainless-steel substrate (Figures 23a and b). V 2 O 5 loaded SnO 2 nanowires exhibit a high rate capability and very good cycling stability ( Figure 23c).…”
Section: Thin Layer Loaded On a Continuous Conductive Matrixmentioning
confidence: 99%